(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Nutritional knowledge and eating habits among healthcare students, particularly nursing students, play a crucial role in shaping their future professional practice and personal health outcomes. Understanding the relationship between nutritional awareness and dietary behaviors is essential for developing effective educational interventions and promoting healthy lifestyle practices within healthcare education institutions. Objective: This study aimed to assess the association between nutritional knowledge and eating habits among students at Sir CJ Institute of Nursing Hyderabad, examining meal consumption patterns, dietary preferences, and factors influencing food choices. Methods: A cross-sectional descriptive study was conducted among nursing students using a structured questionnaire to evaluate eating behaviors, meal patterns, and nutritional awareness. Data were collected on regular meal consumption, breakfast habits, fruit and vegetable intake, sweet consumption, take-out food preferences, home-cooked meal consumption, hydration practices, and understanding of nutritional balance principles. Results: The majority of students (91.7%) reported regular meal consumption, with 70.8% consuming breakfast regularly. However, only 39.2% consumed fruits and vegetables regularly, while 42.5% rarely consumed sweets apart from meals. Take-out food consumption showed mixed patterns (30.0% weekly, 28.3% regular), whereas 65.8% regularly consumed home-prepared meals. Nearly all students (96.7%) maintained adequate daily water intake, and 95.8% acknowledged the importance of nutritionally balanced food, with 81.7% having previously considered nutritional balance concepts. Conclusion: This study was concluded that nursing students demonstrated strong awareness of nutritional principles and maintained regular meal patterns, significant gaps existed between knowledge and practice, particularly regarding fruit and vegetable consumption and meal preparation independence.